Simulasi Rasio dan Proporsi Menggunakan Google Spreadsheet - Muhamad Ihsan Mabruri (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2022)
This research is a type of classroom action research to determine the improvement of student learning outcomes in terms of ratio and proportion using Google Spreadsheet. The problem with grade 6 students at SDN I Bugeman is that students cannot explain correctly when they get a statement that the area of the Indonesian ocean is 23 parts. Utilization of Google Spreadsheet is used as an alternative solution to supporting learning, which students usually use conventional learning into a simulation of mathematics learning. The study was conducted on 18 students through two cycles with each cycle going through four components, namely preparation, action, observation, and reflection. Improved learning outcomes were obtained through student activity observation sheets, pre-test post-tests and student interest questionnaires. The improvement in learning outcomes from Cycle I to Cycle II was seen after students became accustomed to using Google Spreadsheets in learning. The benchmark for the success of this research is to obtain good test results with an average score of at least 70 and learning completeness above 85% classically. Students also gave positive responses based on student response questionnaires during learning.